Understanding the Motives for Terrorism—Does it Have an Effect on Psychological Reactions? A Replication and Extension - Leder, Johannes (Journal of interpersonal violence, 2022)
The collective communication model of terrorism (CCMT) proposes that understanding terrorists? motives influences appraisal (threat perception and emotional well-being) and reaction to terrorism (intention to retaliate). Fischer et al. (2011) presented evidence from two experiments for the assumption that understanding motives of terrorism influences appraisal. The present preregistered experiment aimed to replicate their second experiment, validate the measures they used, and also test the second proposition of the CCMT. Ensuring sufficient power for multiple tests and the given effect size, we collected data from 188 participants. The findings by Fischer et al. (2011) were partly replicated, but the comparison of the original effect sizes and the effect sizes from the replication attempt does not provide convincing evidence for the hypothesis that understanding the motives for terrorism reduces the perceived threat or negative emotional impact of acts of terrorism. Correlations with other risk-perception measures call into question the validity of the items used to assess perceived threat. Results suggest that understanding the motives for terrorism may influence whether the targeted populations want to retaliate.